The CLG Framework: A Methodical Approach to Designing Educational Video Games - Haahr, Mads (Springer Singapore, 2023)
This paper introduces the Context Learning Game (CLG) framework, a game design framework developed for educational video games in formal education settings. The CLG framework is structured into three stages: context, learning, and game. The context stage establishes general game aspects such as the objectives, target audience, and available resources. The learning stage defines formal learning components, including learning theory, content, learning objectives, and learning activities. Finally, the game stage encompasses the formal game elements, development, and testing. The stages are hierarchical, with the context forming the foundation for the learning stage, and both serving as the basis for the game stage. The framework aims to integrate concepts from educational video game design, entertainment game design, and educational design while providing a simple iterative workflow. To illustrate the framework?s potential, a successful case study of an educational game?s design, development, and testing process is presented.
Lecture Notes in Educational Technology (LNET)
Latin American Conference on Learning Technologies (LACLO 2023)
Keywords: educational video game; design framework; design model; Creative Technologies; Digital Engagement; Digital Humanities